Motivational Enhancement: What Ancient Technologies of the Self and Recent Biotechnologies Have in Common - Iftode, Cristian (The new bioethics, 2024)
Motivational enhancement of any kind can be conceived of either as a way to reduce the need for effort, or as a change in the subjective perception of effort. However, in both cases, effort is not all that matters. In the evaluation of praiseworthy conduct, the practical goals pursued by the subject, their dedication, and the discernment they exercise are equally important. I further argue that not only in terms of the general purpose, but also in terms of the means employed for human enhancement, we cannot, in fact, establish significant differences between the traditional technology of the self and biomedical technologies for enhancing motivation. There are two key features they all share. The traditional techniques of the self also aim at the gradual reduction of effort through their steady practice, and they are all mental conditioning and self-conditioning techniques based on repetition and training.